Hubungan Persepsi, Kepuasan dan Loyalitas Pemustaka di Perpustakaan Nasional Republik Indonesia - Tamara, Leli (Universitas Brawijaya, Indonesia, 2014)
This research aims to analyze the relationship between perception, satisfaction and loyalty of the users in the National Library of the Republic of Indonesia. This research was conducted at the National Library of the Republic of Indonesia on closed access services. The Methods of testing instruments were used SPSS Software 16.00 and hypothesis testing used structural equation modeling (SEM) by SmartPLS software. The characteristics of respondents predominantly female (68%), aged 17-25 years (82%), they are working as a student (79%) and Sarjana S1 (76%). Based on the analysis of SEM with PLS approach, we can see the relationship of the six basic elements of the library (electronic resources, printed publications, other services, technical facilities, library environment, the human side) towards the value, satisfaction and loyalty. The results of the study shows that the other services have a significant relationship with the value of the users in the National Library of the Republic of Indonesia. While the variables of human side, environmental and electronic library resources related to the satisfaction in the National Library of the Republic of Indonesia. While the value of users'variables significantly related to the loyalty in the National Library of the Republic of Indonesia. Therefore, it can be concluded that not all of the basic elements of the library have a relationship with the value, satisfaction and loyalty.